Anaerobic digestion development of leaves and petioles of longan waste residue to generate biogas and by products - Panyaping, Klinpratoom; Sutinan, Naparat; Tananchai, Piyanan; Muangkhuanjai, Ukrit (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this study was to develop anaerobic digestion in three different ratios of green (fresh) and brown (dry) leaves and petioles of longan waste residue in order to obtain by products; biogas and other. The low rate digester 200 liters (l) was designed to use for this study. The pig sludge was used as starter for the digestion process of longan waste residue by mixing with the spent wash liquor. Three sets of experiment were carried out during October 2009-June 2010. It was found that the 2nd set (ratio fresh: dry 3:1) produced the maximum quantity of biogas in 14 days (544 l). The quantity of biogas generated was about 40 liters/day consisting of CH4 34%. The quantity of biogas from the 1st set (ratio fresh: dry 4:0) (498.5 l) was similar to that in the 2nd set. The 3rd set (ratio fresh: dry 2:2) produced the minimum quantity of biogas (247.5 l). The good quality of liquid compost that contained essential nutrients; N, P, and K was also obtained. %COD removal from all sets of experiment was in the same range (> 92%). The 2nd set that presented the highest %COD removal was used to operate in the improved digester. It could produce biogas in rainy season, but less than the previous experiments in winter season.